ONE HEALTH – A NEW CONCEPT IN SOCIAL SCIENCES? - Corina BISTRICEANU PANTELIMON; Clara POPA (Anthropological Researches and Studies, 2019)
The present article emphasizes the emergence and spread of a new concept in the scientific field: One Health concept. It refers to the unitary approach of some topics such as risks and crisis originated at the interface between human social world, one hand, and the biological and ecological environments, on the other hand, which, until recently have been addressed in specialized ways. The One Health approach, developed since 2005 as an international and cross-sector movement, recognizes and affirms that human, animal and ecosystem health is interlinked. More than joining ecology, veterinary medicine, human health, microbiology and molecular biology, public health, and health economics, there are arguments that social and socio-behavioral sciences can integrate the concept of One Health into a new explanation about balance and health of the groups and individuals, on the one hand, and imbalance and pathology on the other hand. The traditional specialised way of treating social and cultural pathologies is barely productive. But it can be continued towards a positive approach to social health as a rebalancing of natural and cultural resources. One Health, as a healthcare current and as a model for scientific integrated thinking can include the results obtained in the field of socio-human sciences in order to restore continuity and integration between man, society and environment.